1979
DOI: 10.1007/bf01642151
|View full text |Cite
|
Sign up to set email alerts
|

A comparative trial of pivmecillinam and ampicillin in bacteriuria of pregnancy

Abstract: A comparative trial of pivmecillinam and ampicillin was performed on 100 women with bacteriuria of pregnancy. They received either 400 mg pivmecillinam four times daily or 500 mg ampicillin four times daily for seven days. Cure rates at two weeks were 88% in the pivmecillinam group and 85% in the ampicillin group. At six weeks the respective rates were 76% and 64%. Failure of therapy was not associated with the appearance of bacterial resistance in either treatment group. Side-effects, particularly vomiting an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…We have included five studies examining different antibiotic regimens: Bayrak 2007 compared a single dose of fosfomycin trometamol 3 g with a five-day course of twice daily cefuroxime.In a study reported by Bint 1979, pivmecillinam 400 mg was compared with ampicillin 500 mg. Women in both arms of the trial had antibiotics four times each day for seven days.In the study by Campbell-Brown 1987, a three-day course of cephalexin 1 g twice-daily was compared with Miraxid® (pivmecillinam 200 mg and pivampicillin 250 mg) twice daily for three days.In the most recent and largest trial, a one-day versus a seven-day regimen of nitrofurantoin was compared (Lumbiganon 2009). Women received either nitrofurantoin 100 mg twice for one day (with placebo twice daily for the following six days) or a seven-day course of twice-daily nitrofurantoin.The study by Robertson 1968 compared cycloserine 250 mg given twice a day for 14 days with sulphadimidine 500 mg given for 14 days.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have included five studies examining different antibiotic regimens: Bayrak 2007 compared a single dose of fosfomycin trometamol 3 g with a five-day course of twice daily cefuroxime.In a study reported by Bint 1979, pivmecillinam 400 mg was compared with ampicillin 500 mg. Women in both arms of the trial had antibiotics four times each day for seven days.In the study by Campbell-Brown 1987, a three-day course of cephalexin 1 g twice-daily was compared with Miraxid® (pivmecillinam 200 mg and pivampicillin 250 mg) twice daily for three days.In the most recent and largest trial, a one-day versus a seven-day regimen of nitrofurantoin was compared (Lumbiganon 2009). Women received either nitrofurantoin 100 mg twice for one day (with placebo twice daily for the following six days) or a seven-day course of twice-daily nitrofurantoin.The study by Robertson 1968 compared cycloserine 250 mg given twice a day for 14 days with sulphadimidine 500 mg given for 14 days.…”
Section: Resultsmentioning
confidence: 99%
“…In a study reported by Bint 1979, pivmecillinam 400 mg was compared with ampicillin 500 mg. Women in both arms of the trial had antibiotics four times each day for seven days.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, nalidixic acid and trimethoprim-sulfamethoxazole are not recommended for use in pregnancy. Pivmecillinam has been shown to be effective but was associated with a significantly higher rate of side effects than ampicillin (2).…”
Section: Discussionmentioning
confidence: 99%